(untitled) (Revista Apotheke, 2022)
When thinking about an artistic process in all its (im)possible layers, it is inevitable that there is a constant movement, a coming and going, an erratic wandering connected via feedback in resonances creating bridges and points of departure and arrival, and vice versa: the work being at the same time question and answer in research and artistic practice. In constant deterritorializations and reterritorializations, a heterogeneous network is weaved, a rhizomatic web, without center, beginning or end. Made of line(s) of flight(s), it brings up questions, (re)arrangements and (re)configurations. There is an erratic wandering, a nomadism happening from ground zero to ground zero - these are not fixed themselves -, taking detours from the outside, in the functioning and operation of a kind of system or abstract machine that puts thinking and doing into action, inseparable, although carrying specificities and singularities each – as if in a symbiosis. How does a process take place and when does a process take place? Processes are triggered at each bump between situations: ideas, readings, listening, writing, work. Even so, for this to be triggered and the bump to happen, something must first be set in motion: other situations – starting a wandering, walking, a nomadism not necessarily involving a displacement of the body, but which can happen on a shelf, even in a writing process. Such a movement is what propels, in a feedback loop, a process to operate – inseparable from the movement and nomadism’s of the lines of flight shot from the bumps: germinators of means, zero marks, crossing points. A nomadic process overflows margins of error: not of error as erasure (although the idea is interesting to investigate), but of error as errancy. Margins of error, when punctured by the limping and nomadic walk of the researcher artist, give vent to vibrations, reverberations and resonances.